Organic Catalysis for Polymerisation 2018
DOI: 10.1039/9781788015738-00087
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional and Supramolecular Organocatalysts for Polymerization

Abstract: Bimolecular, H-bond mediated catalysts for ring-opening polymerization (ROP)—thiourea or urea plus base, squaramides and protic acid/base pairs, among others—are unified in a conceptual approach of applying a mild Lewis acid plus mild Lewis base to effect ROP. The bimolecular, and other supramolecular catalysts for ROP, produce among the best-defined materials available via synthetic polymer chemistry through a delicately balanced series of competing chemical reactions by interacting with substrate at an energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 144 publications
1
8
0
Order By: Relevance
“…The ROP are living in behavior, both 2-S5 and 2-O5 plus MTBD produce linear evolution of M n versus conversion (Figure ) and M n that is predictable by [M] o /[I] o (Table S1). In C 6 D 6 (and other non-polar solvents), an H-bond-mediated mechanism of enchainment has been proposed; ,, urea plus base-mediated ROP has been shown to display faster rates than the analogous thiourea (Table ). , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ROP are living in behavior, both 2-S5 and 2-O5 plus MTBD produce linear evolution of M n versus conversion (Figure ) and M n that is predictable by [M] o /[I] o (Table S1). In C 6 D 6 (and other non-polar solvents), an H-bond-mediated mechanism of enchainment has been proposed; ,, urea plus base-mediated ROP has been shown to display faster rates than the analogous thiourea (Table ). , …”
Section: Resultsmentioning
confidence: 99%
“…H-bonding organocatalysts for ring-opening polymerization (ROP) are a facile means of generating precisely tailored macromolecules. Among the larger class of H-bonding organocatalysts, (thio)­urea H-bond donors stand out for the remarkable level of control they can render in polymer synthesis. , The thiourea plus base-mediated ROP of lactone and carbonate monomers are thought to effect enchainment by H-bond activation of monomer by thiourea and initiating/propagating chain end by base; these catalysts are most active in a nonpolar solvent . The urea plus base class of H-bonding catalysts are among the most active catalysts for the ROP of lactones. Several mechanistic studies by our group and others have shown that (thio)­urea/base-mediated ROP can proceed by one of two mechanisms: neutral H-bonding or (thio)­imidate-mediated ROP (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5] This class of catalysts, often an H-bond donating (thio)urea plus an H-bond accepting organic base, are believed to effect ROP by H-bond activation of a lactone monomer and alcohol chain-end/initiator. 5,6 More recently, (thio)urea/base-mediated ROP has been found to access an alternate mechanism of enchainment whereby proton transfer from (thio)urea to the base produces a highly active (thio) imidate that is among the most active and controlled catalysts for the ROP of lactones, carbonates and other cyclic monomers. [7][8][9][10] Of particular importance here is the highly controlled aspect of the (thio)urea/base-mediated ROP, which allows for the polymerization of functionalized and heteroatom-containing monomers while retaining polymerization control.…”
Section: Introductionmentioning
confidence: 99%